The fuel cells studies from ionic electrolyte Ce0.8Sm0.05Ca0.15O2−δ to the mixture layers with semiconductor Ni0.8Co0.15Al0.05LiO2−δ. (2nd November 2016) - Zhang, Wei; Cai, Yixiao; Wang, Baoyuan; Deng, Hui; Feng, Chu; Dong, Wenjing; Li, Junjiao; Zhu, Bin
Abstract: The mixture of ionic electrolyte Ce0.8 Sm0.05 Ca0.15 O2−δ (SCDC) and semiconductor Ni0.8 Co0.15 Al0.05 LiO2−δ (NCAL) layers was used for low temperature solid oxide fuel cell (LT-SOFC) applications. Using the as-prepared SCDC-NCAL semiconductor-ionic layer to replace the ionic SCDC electrolyte, following results have been obtained: the SCDC electrolyte fuel cell reached a lower voltage, 1.05 V, and lower power output, 415 mW cm −2, compared to that using the semiconductor-ionic layer, 1.06 V and 617 mW cm −2 at 550 °C. The electrochemical impedance spectroscopy (EIS) was applied to investigate the electrochemical processes of the device; X-ray diffraction (XRD) and field emission scanning electron microscope (FE-SEM) for the microstructure and morphology of the as-prepared materials. The results have illuminated that the introduction of semiconductor into ionic electrolyte could make extended triple phase boundary (TPB) area, which can provide more active sites to accelerate the fuel cell reactions and enhance the cell performance. Furthermore, we also discovered that the ionic SCDC and electronic NCAL should be in an appropriate composition to achieve a balanced ionic and electronic conductivity, which is the key issue for high performance semiconductor-ionic fuel cells. Highlights: A new SCDC-NCAL functional semiconductor-ionic composite material. Its replacement of the electrolyte for fuel cells with better performances. Ratios between SCDC and NCAL with significant effect on fuel cells. The device with 30 wt.% NCAL obtained 617 mW cm −2 at 550 °C.